2013
DOI: 10.1111/imb.12031
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee promoter sequences for targeted gene expression

Abstract: The honey bee, Apis mellifera, displays a rich behavioural repertoire, social organization and caste differentiation, and has an interesting mode of sex determination, but we still know little about its underlying genetic programs. We lack stable transgenic tools in honey bees that would allow genetic control of gene activity in stable transgenic lines. As an initial step towards a transgenic method, we identified promoter sequences in the honey bee that can drive constitutive, tissue-specific and cold shock-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The offspring of those transformed queens efficiently expressed the transgenic markers from the 6xP3 promoter (31) and the endogenous promoter Am-actin5c (32). We analyzed at least 34 offspring of each [6xP3-rubia] queen and found that all of the offspring that possessed the transgene were also expressing the transgenic marker (43,6,30, and 9% progeny of the different queens).…”
Section: Resultsmentioning
confidence: 99%
“…The offspring of those transformed queens efficiently expressed the transgenic markers from the 6xP3 promoter (31) and the endogenous promoter Am-actin5c (32). We analyzed at least 34 offspring of each [6xP3-rubia] queen and found that all of the offspring that possessed the transgene were also expressing the transgenic marker (43,6,30, and 9% progeny of the different queens).…”
Section: Resultsmentioning
confidence: 99%
“…It could be that systemic RNAi is not readily achievable in honey bees -indeed, one of the only examples of systemic RNAi in honey bees is from an experiment where the dsRNA corresponds to a honey bee virus, rather than the bees' own genes (17). We are therefore pursuing transgenics as a method of manipulating gene expression in honey bees (18), with the ultimate goal of determining a relationship between OBP expression and death or disease odor detection.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al (2000) attempted to transfect linearized plasmid mixed with sperm into fertilized eggs by the artificial insemination of virgin queens, and reported that the external DNA was propagated for at least three generations, although integration of the transfected DNA into the genome was not detected [47]. Kunieda et al (2004) and Schulte et al (2013) used electroporation to transfect a plasmid into the honey bee brain [48,49]. They confirmed the expression of the external gene ( green fluorescent protein : GFP ) in the brains of transfected bees by immunoblotting or immunohistochemistry using an anti-GFP antibody [48,49].…”
Section: Genetic Methods Applied To the Honey Beementioning
confidence: 99%